Ikaite formation in streams affected by steel waste leachate: First report and potential impact on contaminant dynamics - Laura Bastianini; Mike Rogerson; Alex Brasier; Timothy J. Prior; Kit Hardman; Eddie Dempsey; Anna Bird; William M. Mayes (Chemical Geology, 2024)

Symbiotic ant traits produce differential host‐plant carbon and water dynamics in a multi‐species mutualism - Patrick D. Milligan; Timothy A. Martin; Elizabeth G. Pringle; Kirsten M. Prior; Todd M. Palmer (Ecology, 2023)
Cooperative interactions may frequently be reinforced by “partner fidelity feedback,” in which high‐ or low‐quality partners drive positive feedbacks with high or low benefits for the host, respectively. Benefits of plant–animal mutualisms for plants have been quantified almost universally in terms of growth or reproduction, but these are only two of many sinks to which a host‐plant allocates its resources. By investigating how partners to host‐plants impact two fundamental plant resources, carbon and water, we can better characterize plant–partner fidelity and understand how plant–partner mutualisms may be modulated by resource dynamics. In Laikipia, Kenya, four ant species compete for Acacia drepanolobium host‐plants. These ants differ in multiple traits, from nectar consumption to host‐plant protection. Using a 5‐year ant removal experiment, we compared carbon fixation, leaf water status, and stem non‐structural carbohydrate concentrations for adult ant–plants with and without ant partners. Removal treatments showed that the ants differentially mediate tree carbon and/or water resources. All three ant species known to be aggressive against herbivores were linked to benefits for host‐plant resources, but only the two species that defend but do not prune the host, Crematogaster mimosae and Tetraponera penzigi , increased tree carbon fixation. Of these two species, only the nectivore C. mimosae increased tree simple sugars. Crematogaster nigriceps , which defends the tree but also castrates flowers and prunes meristems, was linked only to lower tree water stress approximated by pre‐dawn leaf water potential. In contrast to those defensive ants, Crematogaster sjostedti , a poor defender that displaces other ants, was linked to lower tree carbon fixation. Comparing the effects of the four ant species across control trees suggests that differential ant occupancy drives substantial differences in carbon and water supply among host trees. Our results highlight that ant partners can positively or negatively impact carbon and/or water relations for their host‐plant, and we discuss the likelihood that carbon‐ and water‐related partner fidelity feedback loops occur across ant–plant mutualisms.

Rethinking the interplay between affluence and vulnerability to aid climate change adaptive capacity - Christine Eriksen; Gregory L. Simon; Florian Roth; Shefali Juneja Lakhina; Ben Wisner; Carolina Adler; Frank Thomalla; Anna Scolobig; Kate Brady; Michael Bründl; Florian Neisser; Maree Grenfell; et al. (Climatic Change, 2020)
Affluence and vulnerability are often seen as opposite sides of a coin—with affluence generally understood as reducing forms of vulnerability through increased resilience and adaptive capacity. However, in the context of climate change and an increase in associated hazards and disasters, we suggest the need to re-examine this dynamic relationship—a complex association we define here as the Affluence–Vulnerability Interface (AVI). We review research in different national contexts to show how a more nuanced understanding of the AVI can (a) problematize the notion that increasing material affluence necessarily has a mitigating influence on social vulnerability, (b) extend our analysis of social vulnerability beyond low-income regions to include affluent contexts and (c) improve our understanding of how psychosocial characteristics influence people’s vulnerability. Finally, we briefly outline three methodological approaches that we believe will assist future engagement with the AVI.

From desert to rainforest, sapwood width is similar in the widespread conifer Callitris columellaris - Lynda D. Prior; Timothy J. Brodribb; David Y. P. Tng; David M. J. S. Bowman (Trees, 2013)

Peak Minerals: Theoretical Foundations and Practical Application - Daniel May; Timothy Prior; Dana Cordell; Damien Giurco (Natural Resources Research, 2012)

Continental-scale climatic drivers of growth ring variability in an Australian conifer - David M. J. S. Bowman; Lynda D. Prior; David Y. P. Tng; Quan Hua; Timothy J. Brodribb (Trees, 2011)